2019
DOI: 10.1111/jocn.15106
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an assessment tool for nursing workload in emergency departments

Abstract: Aims To develop the Workload Assessment of Nurses on Emergency (WANE) tool and to test its validity and reliability to measure nursing workload in the emergency departments. Background Ensuring safe nursing staffing in emergency departments is a worldwide concern. There is no valid tool to measure emergency nursing workload in order to determine the needed nurse staffing in the emergency departments. Design A two‐year, cross‐sectional, multicenter study. Methods Workload was operationalised as the time nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…As in Study 1, this study considers the role of job demands (bullying) and resources (perceived organizational, supervisor, and colleagues support) in the prediction of workers' likelihood of membership into the profiles. In this study, the decision was made to replace workload, known to be systematically elevated for most nurses (Iordache et al, 2020), as a job demand indicator. Bullying was retained based on previous results supporting its importance in the nursing profession (Johnson, 2009) and association with recovery (Rodríguez-Muñoz et al, 2017).…”
Section: Brief Discussionmentioning
confidence: 99%
“…As in Study 1, this study considers the role of job demands (bullying) and resources (perceived organizational, supervisor, and colleagues support) in the prediction of workers' likelihood of membership into the profiles. In this study, the decision was made to replace workload, known to be systematically elevated for most nurses (Iordache et al, 2020), as a job demand indicator. Bullying was retained based on previous results supporting its importance in the nursing profession (Johnson, 2009) and association with recovery (Rodríguez-Muñoz et al, 2017).…”
Section: Brief Discussionmentioning
confidence: 99%
“…To assess staffing levels in hospital settings, commonly used variables include numbers of nursing hours per patient day and nurse–patient ratios (Min & Scott, 2016). Another variable used in emergency care settings is nursing hours per patient (Ramsey et al., 2018), and others used in emergency care nurse staffing models include nursing hours, staffing levels and patients' acuity levels (Lordache, Elseviers, De Cock, & van Rompaey, 2020; Otegbeye, Scriber, Ducoin, & Glasofer, 2015). According to interviewed emergency nurses, safe staffing determinations should not be based solely on numbers of patient beds, but also on information regarding patient acuity and volume as well as experience mix of the nursing staff (Wolf, Perhats, Delao, Clark, & Moon, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire adopted in this study consists four parts: Basic personal data: The data include gender, age, years of service, educational level, nursing ability level, use ability of IT products, and unit type. Nurse Workload Scale: In terms of factors related to nurses’ job satisfaction, studies have found that nursing workload is significantly and negatively correlated with job satisfaction, that is, the heavier the workload, the worse the job satisfaction [ 30 ]. This study referred to Tsai and Chen’s “Taiwan Hospital Nursing Staff Stress Scale” [ 9 ], which was modified from Benoliel et al [ 31 ].…”
Section: Methodsmentioning
confidence: 99%